Pippo learns a lesson: a book about being kind to others (Educational Technologies Ltd Place of publication not identified, 2004)
"Pippo Learns a Lesson: A Book About Being Kind to Others" is a heartwarming tale about a mischievous little squirrel named Pippo, who often plays tricks on his forest friends without realizing how it hurts them. One day, after a prank goes too far, Pippo sees how upset his friends are and feels bad for his actions. With the help of a wise owl, Pippo learns the importance of kindness, empathy, and treating others the way he wants to be treated. The story highlights how small acts of kindness can strengthen friendships and make the world a better place.